1994
DOI: 10.3109/15513819409023331
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Femoral Hypoplasia and Maternal Diabetes Mellitus: Case Report and Review of the Literature

Abstract: The case of a 21-week fetus with bilateral femoral hypoplasia and bowing related to maternal diabetes mellitus is reported. The femoral middiaphysis (site of hypoplasia and bowing) showed intramembranous ossification instead of the normal endochondral ossification, thus pointing to a transient inhibition of chondrogenesis of the mesenchymal femoral model as the causative mechanism. This finding is correlated with the recent experimental advances in the field of limb development in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Findings by Hitti et al (1994) lend further support to this theory, with an intriguing discussion of macroscopic and microscopic aspects of femoral bowing and shortening in a fetus. Macroscopically, the deformity is bilateral and symmetrical in appearance, affects the middle of the diaphysis, and is not associated with other anomalies.…”
Section: Differential Diagnosismentioning
confidence: 76%
See 1 more Smart Citation
“…Findings by Hitti et al (1994) lend further support to this theory, with an intriguing discussion of macroscopic and microscopic aspects of femoral bowing and shortening in a fetus. Macroscopically, the deformity is bilateral and symmetrical in appearance, affects the middle of the diaphysis, and is not associated with other anomalies.…”
Section: Differential Diagnosismentioning
confidence: 76%
“…This scenario, rather than an early bilateral fracture, represents a more likely cause of the Sunghir 3 femoral deformities, and provides a better explanation of their localized, symmetrical appearance. Interestingly, Hitti et al (1994) suggested a link between the observed inhibition of chondrogenesis shown by the fetus and the diabetic condition of the mother. Experimental observations and clinical data demonstrated that abnormal glucose levels are deleterious to cartilage development (Leonard et al, 1989), and that infants of diabetic mothers are subject to delayed ossification and skeletal defects, especially in bones of endochondral ossification (Kucera, 1971; Jovanovic et al, 1986).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Hitti et al, 7 were the first to present a detailed histopathological examination of aborted fetus with congenital femoral hypoplasia of a diabetic mother. 7 The primitive mesenchyme cells derived from the lateral plate are destined to form the skeleton and tendons of the lower limb through transformation to a cartilaginous model that can undergo endochondralossification to form the tubular shape of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…7 The primitive mesenchyme cells derived from the lateral plate are destined to form the skeleton and tendons of the lower limb through transformation to a cartilaginous model that can undergo endochondralossification to form the tubular shape of the femur. Hitti et al, 7 showed that at certain segment or focus of the diaphysis of the growing femur during embryogenesis the mesenchyme cells skip the cartilaginous transformation and get transformed into bone directly through intermembraneous ossification, this bony part is more or less flat, lacking the normal tubular architecture of the rest of femur, hence the name focal femoral deficiency. It is known that the cartilaginous development is sensitive to the level of glucose, 8 the abnormal glucose level selectively inhibit cartilage-specific proteoglycan core protein gene.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a frequent overlap of clinical manifestations, it has been suggested that short femur is a part of a developmental field defect including femur-fibula-ulna syndrome, fibula aplasia-hypoplasia, and femoral hypoplasia/unusual syndrome [11]. Other possible etiological factors are maternal diabetes mellitus, drugs such as thalidomide, radiation, focal ischemia, or trauma occurring between the 4th and 8th weeks of gestation [1,12,13].…”
Section: Discussionmentioning
confidence: 99%